Percy Jackson : And the olympians - RIORDAN,RICK (Los Angeles : Disney Hyperion, 2023)
Percy Jackson's hope for a normal senior year is shattered as the gods present him with three quests, beginning with the retrieval of Zeus's goblet, in order to get the necessary three letters of recommendation for college
Keywords: English - Fictional book